Results of an international survey on the current organization of care for pregnant women with cancer - Joosje H. Heimovaara; Kristel vanCalsteren; Christianne A. R. Lok; Andrew M. Evens; Jorge Hoegl; Andres Ferber; Andreina Fernandes; Ingeborg Vriens; Lia vanZuylen; Frédéric Amant (Acta Obstetricia et Gynecologica Scandinavica)
Abstract The global incidence of cancer is increasing, including its incidence in women of reproductive age. Still, physicians encounter this situation rarely, which could lead to substandard care. This research sought to explore opportunities to improve future care for pregnant women with cancer, by describing the outcomes of a survey distributed to physicians all over the world focusing on clinical experience with pregnant women with cancer, the organization of care and current gaps in knowledge. We included 249 responses from physicians working across 36 countries. Responses demonstrate a wide variation in the organization of care – generally lacking centralization, and the physicians' acknowledgement of insufficient knowledge on the management of pregnant women with cancer. There is a need for improvement through national centralization and/or establishing advisory boards for cancer in pregnancy. Seeing the paucity of cancer in pregnancy experience, the importance of global multidisciplinary collaboration is emphasized.